2017
DOI: 10.1002/cam4.996
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of tumor‐suppressive microRNA, miR‐126, in chronic lymphocytic leukemia

Abstract: The introduction of miR profiling of chronic lymphocytic leukemia (CLL) patients with different cytogenetic profiles and responses to therapy has allowed incorporation of important miR‐mRNA interactions into the understanding of disease biology. In this study, we performed miR expression analysis using NanoString nCounter to discover differentially regulated miRs after therapy with the Bruton tyrosine kinase inhibitor ibrutinib. Of the differentially regulated miRs in the discovery set, miR‐29c and miR‐126 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…miRNAs have been reported to be the biomarkers of cancer detection and have directly or indirectly relation with tumorigenesis and further development [38]. Previous study showed that miR-126, a tumor suppressor, promotes apoptosis or induced proliferation repression in many kinds of caners [3941] and also was reported to target GOLPH3 to suppress proliferation, migration and invasion in esophageal squamous cell carcinoma [20]. In gastric cancer cells miR-134 suppresses cell proliferation via targeting of GOLPH3 [42].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been reported to be the biomarkers of cancer detection and have directly or indirectly relation with tumorigenesis and further development [38]. Previous study showed that miR-126, a tumor suppressor, promotes apoptosis or induced proliferation repression in many kinds of caners [3941] and also was reported to target GOLPH3 to suppress proliferation, migration and invasion in esophageal squamous cell carcinoma [20]. In gastric cancer cells miR-134 suppresses cell proliferation via targeting of GOLPH3 [42].…”
Section: Discussionmentioning
confidence: 99%
“…Through these processes, miR-126 plays a role in cancer and autoimmune biology. The microRNA 126 was shown to have important roles in cancers of the gastrointestinal and genital tracts, in the cancers of the breast, the thyroid, the lung and in some other ones [ 8 14 ]. Usually, miR-126 is down-regulated in tumours, most likely due to its ability to inhibit malignant cell growth, adhesion, migration, and invasion through suppressing a range of important target genes.…”
Section: Autoimmune Diseases Related To Mir-126mentioning
confidence: 99%
“…Therefore, high expression of miR-21-5p leads to an upregulation of MAPK/ERK signaling and a relative result to survival and proliferation of the leukemic B cells [ 63 ]. However, tumor-suppressive miRNAs which contribute negatively to the MAPK/ERK signaling pathway have also been identified in B-CLL [ 64 , 65 ]. As described previously, miRNAs are also involved in the regulation of the PI3K/AKT pathway, either by directly influencing the pathway or by downregulating the expression of PTEN, a tumor suppressor of this pathway [ 66 , 67 ].…”
Section: Mirnas: Regulators Biomarkers and Potential Therapeutic mentioning
confidence: 99%